Laboratory Research of the Controllable Hydraulic Damper - Konieczny, Jarosław; Kowal, Janusz; Pluta, Janusz; Podsiadło, Andrzej (Engineering Transactions, 2006)
The main focus is on the hydraulic shock absorbers employed in vehicles, in the context of parameters associated with the damping force control for the given direction of action and with the energy dispersion. Two types of shock absorbers are examined: those with constant and variable parameters of damping force adjustment. Shock absorbers that were subject to research investigations included a commercially — available shock absorber with fixed parameters and an experimental absorber with variable parameters. The paper summarises the problems experienced during modelling of hydraulic shock absorbers when the equivalent damping ratio is sought. Damper properties and the methods of determining them are outlined. The laboratory tests performed on these shock absorbers are considered in more detail and relevant characteristics are provided for the sake of comparison. The reasons why shock absorbers with fixed parameters have been in widespread use for many years are now investigated, highlighting the aspects which prompt the research work on shock absorbers with variable parameters.